The evaluation of kLa values for recombinant Escherichia coli fermentation producing β-Glucuronidase enzyme - Mel, Maizirwan; Abdul Karim, Mohamed Ismail; Mohd. Salleh, Hamzah (Asian Network for Scientific Information, 2010)
This study is focused on the evaluation of the vohnnetric mass transfer coefficient (kLa) of E. coli fermentation producing ~-glucuronidase enzyme in different bioreactor operating conditions. The operating conditions used were according to the Taguchi's method design using three factors of fermentation viz., temperature, agitation speed and air flow rate at two concentration levels. From the four experiments conducted, experimental nul mnnber two with agitation of 300 rpm, airflow rate of 2 vvrn and temperature 41°C generate the highest Optical Density (OD 660 nrn) of 2.313 for cell count and also having an equivalent k,a value of 0.0281 min-lor 1.686 h-1.This condition was fOlllld to be an effective point for upscaling in bigger bioreactor for E. coli fermentation to produce the enzyme.